2017
DOI: 10.3389/fneur.2017.00461
|View full text |Cite
|
Sign up to set email alerts
|

Pain in People with Multiple Sclerosis: Associations with Modifiable Lifestyle Factors, Fatigue, Depression, Anxiety, and Mental Health Quality of Life

Abstract: BackgroundPeople with multiple sclerosis (MS) often experience pain, which can interfere with mobility, employment, and quality of life (QOL).MethodsThis cross-sectional study explored associations between pain, demographic, disease, and modifiable lifestyle factors in an international sample of people with MS recruited online.ResultsSubstantial pain, of moderate/severe intensity and interfering at least moderately with work/household or enjoyment of life in the past 4 weeks, was reported by 682/2,362 (28.9%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 53 publications
0
55
0
3
Order By: Relevance
“…A previous study reported a similar incidence of fatigue in NMOSD and MS patients, with a strong correlation between depression and fatigue [9]. On the other hand, chronic pain is a common symptom causing deterioration of activities of the daily living in patients with MS and NMOSD [15][16][17]. However, the relationship between fatigue and pain has not been fully investigated, particularly in NMOSD patients.…”
Section: Introductionmentioning
confidence: 96%
“…A previous study reported a similar incidence of fatigue in NMOSD and MS patients, with a strong correlation between depression and fatigue [9]. On the other hand, chronic pain is a common symptom causing deterioration of activities of the daily living in patients with MS and NMOSD [15][16][17]. However, the relationship between fatigue and pain has not been fully investigated, particularly in NMOSD patients.…”
Section: Introductionmentioning
confidence: 96%
“…Depending on its severity, MS can limit the daily activities of patients and end up producing a relevant degree of disability. Hence, it is the main reason for non-traumatic, invalidating neurological disease in young adults, and is the principal cause of disability acquired between 20 and 40 years of age ( 1 , 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Die Sport-und Bewegungstherapie ist also eine zentrale Komponente des multidisziplinären Ansatzes, mit einer hohen Bedeutung für die Alltagsaktivität. Auch zeigten Marck et al [13], dass modifizierbare Lebensstilfaktoren wie Rauchen, Übergewicht und Bewegung einen Einfluss auf Schmerzen bei MS haben. Einer Adaptation des Gesundheitsverhaltens kommt also bei der Erkrankung MS eine große Bedeutung zu.…”
unclassified